Micro-Raman studies of strain in bulk GaN crystals grown by hydride vapor phase epitaxy on ammonothermal GaN seeds. (23rd May 2019) - Amilusik, M.; Wlodarczyk, D.; Suchocki, A.; Bockowski, M.
Abstract: Raman spectroscopy was used for studying strains in bulk GaN crystallized by HVPE on ammonothermally synthesized seeds. Two types of materials were examined in detail by Raman scattering before and after plastic deformation. Shifts of A1 (TO), E1 (TO), and E 2 high phonon lines were analyzed to determine strain and then stress tensors. Three areas were investigated in each sample: the seed, the crystal grown in the c-direction, and material laterally grown from the edges (wing). In this paper, differences in Raman spectra measured in these parts are shown and described in detail.